Hércules possuído: produto poético de uma leitura crítica ou uma tradução possível do Hercules Furens de Sêneca - Ana Ribeiro Grossi Araujo (2011)
This study contains a complete translation of the Senecan play Hercules Furens, sided by a preface, a map and a glossary of mythological names and expressions referred to in the play. The translation, named Hércules Possuído, tries to get poetic and dramatic aspects of the Latin text and recreate them into Brazilian Portuguese, amplifying access to the text in its most important characteristics. The translation is understood itself as criticism, and sided by theoretical essays. The first theoretical essay focuses on the Roman theater upto first century; Senecan life and works; political and philosophical aspects of the author's life, and Senecan tragedies. The second essay discusses the publishing of Senecan tragedies at his time and their performance in the recitationes, as well as the Senecan tragedies in western dramatic tradition. The last chapter focuses the poetic translation and the questions it demands, as mythological references and the translation of the names; translation of abstract vocabulary, such as uirtus and furor; translation of metrical verses; formal and functional translation of the meters. There is also a graphic scanning of each verse of the play.